Peran Pemerintah Daerah dalam Penanggulangan Tindak Pidana Kekerasan Seksual - Kresna Bayu (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The violence that occurs in Indonesia never stops and even becomes more frequent as time goes by. In general, those who become victims of violence are helpless people such as women and children. On the other hand, with the increasing use of social media, a new form of sexual exploitation is developing known as online child sexual exploitation. This phenomenon shows that the handling of cases of sexual disclosure in Indonesia still does not focus on the needs of victims, which are very important for psychological and physical recovery for victims of sexual understanding. For this reason, the aim of this research is to understand the role of local government in dealing with criminal acts of sexual violence. The type of research that will be used in writing this thesis is the empirical method. This method will examine law with the concept of real behavior as a social phenomenon experienced by everyone in social life. So, for the reasons above, this research aims to find out the role of local government in dealing with violent crime.